2019
DOI: 10.18060/22075
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Practicing Social Workers Define Evidence-Based Practice

Abstract: This research note presents findings from a study that sought to garner a better understanding of the way in which practicing social workers defined Evidence-Based Practice (EBP). As part of a larger quantitative study, 137 social work practitioners provided a definition for EBP through an online survey and indicated the extent to which they: consider themselves an evidence-based practitioner; believe practitioners should apply EBP in social work; and were prepared through their social work education to use EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…van der Zwet et al 2019found that social workers and staff in a social work organization in the Netherlands were confused about EBP, some describing it as interventions that has scientific evidence, others as research-supported treatments, while others included professional expertise and/or client circumstances. Similar results were found in the study by Chonody and Teater (2019) where 137 social workers were questioned about their stance on EBP. The results demonstrated that the social workers identified themselves, somewhat, as an evidence-based practitioner, yet they described EBP as an intervention rather than a process.…”
Section: Previous Research On Social Workers Attitudes Toward Ebpsupporting
confidence: 88%
“…van der Zwet et al 2019found that social workers and staff in a social work organization in the Netherlands were confused about EBP, some describing it as interventions that has scientific evidence, others as research-supported treatments, while others included professional expertise and/or client circumstances. Similar results were found in the study by Chonody and Teater (2019) where 137 social workers were questioned about their stance on EBP. The results demonstrated that the social workers identified themselves, somewhat, as an evidence-based practitioner, yet they described EBP as an intervention rather than a process.…”
Section: Previous Research On Social Workers Attitudes Toward Ebpsupporting
confidence: 88%
“…Based on previous research, practitioners understand and define EBP in varying ways (e.g., Avby et al, 2014;Bergmark & Lundström, 2011;Chonody & Teater, 2018;Heiwe et al, 2013). Varying conceptualizations of EBP provide a rationale for further research on practitioners' perspectives and experiences of EBP and associated models.…”
Section: Changes In the Welfare State Affecting Everyday Practicementioning
confidence: 99%
“…Many studies have discussed and promoted the incorporation of EBP into social work practice (Soydan & Palinkas, 2014). However, there are still challenges and barriers to integrating EBP into social work practice from both social workers and their organisational context (Chonody & Teater, 2018; Gray et al., 2013; Gray, Joy, Plath, & Webb, 2015; Tuten, Morris‐Compton, Abrefa‐Gyan, Hwang, & Harrington, 2016). The mechanism for promoting EBP implementation by social workers has not been clearly studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although many demographic factors, such as age, gender and ethnicity, may influence practitioners' EBPA, education, training and professional experience have received more attention as factors associated with EBPA and EBP implementation (Aarons, 2005; Chonody & Teater, 2018; Marques et al., 2016; Wike et al., 2014). For social workers, EBP has been viewed as a kind of PC through which developmental and dynamic abilities are derived from continuous learning, thus allowing for the integration and application of knowledge and skills in practice in real situations (CSWE, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%